2009
DOI: 10.1242/dmm.003178
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and Parkinson’s disease genes: insights from Drosophila

Abstract: Parkinson’s disease (PD), one of the most common neurodegenerative disorders worldwide, currently lacks a cure. Although most PD cases occur sporadically, studies from rare genetic mutations give significant insights into addressing the pathological mechanism of not only familial PD, but also sporadic PD. Recent PD research focuses on generating genetic mutant animal models that recapitulate the features of human PD patients. Significant advances in PD research have resulted from studying Drosophila mutants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…4). These data clearly showed that Sir2 and FOXO have protective roles in DA neuron and the indirect flight muscle, tissues with high demand for ATP generated by mitochondria (48). Because these defects were observed in 15-or 30-day-old flies, some may argue that these defects in Sir2 or FOXO mutants result from premature aging induced by loss of two genes.…”
Section: Discussionmentioning
confidence: 76%
“…4). These data clearly showed that Sir2 and FOXO have protective roles in DA neuron and the indirect flight muscle, tissues with high demand for ATP generated by mitochondria (48). Because these defects were observed in 15-or 30-day-old flies, some may argue that these defects in Sir2 or FOXO mutants result from premature aging induced by loss of two genes.…”
Section: Discussionmentioning
confidence: 76%
“…parkin, DJ-1, PINK::see http://superfly.ucsd.edu for further information). This unique feature has already led to a better understanding of how these genes work in the human [15,16]. Second, the expression of PD related genes in Drosophila can be performed by using the binary GAL4-dependent upstream activating sequence (GAL4/UAS) system [17], thus providing an excellent tool to express pathological proteins in the fly 0 s brain (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Parkin mediates selective autophagy of dysfunctional mitochondria (mitophagy) as a result of loss of mitochondrial membrane potential or imbalance of mitochondrial dynamics [4,103,104,105,106]. Parkin interacts with PINK1 to control mitochondrial degradation [107], while PARKIN mutations prevent normal mitophagy [108].…”
Section: Parkin and Mitochondrial Functionmentioning
confidence: 99%